Implementasi Pendekatan Andragogi untuk Meningkatkan Keterampilan Belajar Kolaboratif Peserta Didik pada Kelas Bahasa Inggris di Komunitas Belajar Studyteen - Fanny Martha Roesmayanti; Sjafiatul Mardliyah (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2026)
English language learning aims not only to improve students’ language proficiency but also to develop collaborative learning skills that support the learning process. One approach that can facilitate this goal is the andragogical approach, which emphasises learner autonomy, learning experiences, and active participation. Studyteen, a non-formal learning community, implements English language learning through participatory and collaborative activities. This study aims to describe the implementation of the andragogical approach in English language learning, students’ collaborative learning skills, and the role of the andragogical approach in enhancing students’ collaborative learning skills within the Studyteen learning community. This study employed a descriptive qualitative approach. The findings revealed that the implementation of the andragogical approach in English language learning at Studyteen was reflected in voluntary participation, learner-centred learning, the utilisation of learners’ experiences as learning resources, and the tutor’s role as a facilitator. Students’ collaborative learning skills were demonstrated through active participation, individual and group responsibility, meaningful interaction, and the development of social and communication skills throughout the learning process. Furthermore, the andragogical approach contributed to the enhancement of collaborative learning skills by providing learning autonomy, creating a safe and supportive learning environment, and encouraging students to interact and collaborate during English language learning activities.